From Information Exposure to Protective Behaviors: Investigating the Underlying Mechanism in COVID-19 Outbreak Using Social Amplification Theory and Extended Parallel Process Model - Zhao, Shuguang; Wu, Xuan (Frontiers in Psychology, 2021)
Ever since the outbreak of coronavirus disease (COVID-19), people have been flooded with vast amounts of information related to the virus and its social consequences. This paper draws on social amplification theory and the extended parallel process model and assesses the following: a) how two amplification stations—news media and peoples’ personal networks—influence the risk-related perceptions of people (perceived efficacy and perceived threat) and b) how these risk-related perceptions impact people’s health protective behaviors. This study surveyed 1,946 participants. The results indicate that peoples’ exposure to news media significantly and positively predicted both perceived efficacy and perceived threat. It also shows that peoples’ exposure to risk-related information through their personal networks negatively predicted their perceived efficacy, but it positively predicts their perceived threat. The mediating effect of fear was examined, and the result was contradictory to the EPPM. In short, this study reveals the underlying mechanism of individuals’ exposure to risk information, processing, and precautionary measures.